An empirical analysis on consumer adoption of mobile phone and mobile content in Korea. (1st October 2010) - Park, Yuri; Kim, Hyunnam; Lee, Jongsu
This paper aims to empirically analyse consumer preference for mobile phone and mobile content. It is concerned with three issues: how users value the attributes of mobile phones; the effects of demographic characteristics on the adoption of mobile content; the relation between the adoption of mobile phone and mobile content. Discrete-choice model is used for analysing consumer choice data collected from the survey. The results show that touch-screen and full web browsers are preferred and the consumption pattern of mobile content is different according to individual characteristics. There are significant correlations between the adoption of mobile phone and mobile content. Mobile phone that supports full browsing has positive correlations with mobile contents. The findings suggest that mobile phone with particular feature is needed to promote use of mobile content.